The Role of Copper in Tau-Related Pathology in Alzheimer’s Disease - Zubčić, Klara; Hof, Patrick R.; Šimić, Goran; Jazvinšćak Jembrek, Maja (Frontiers in Molecular Neuroscience, 2020)
Various forms of tauopathies, including Alzheimer's disease (AD), are characterized by the intracellular accumulation of abnormal forms of tau protein in neurons and glial cells, which negatively affects microtubule stability. Under physiological conditions tau protein is intrinsically disordered, almost without secondary structure, and is not prone to aggregation. In AD, it assembles, and forms paired helical filaments (PHFs) that further build up neurofibrillary tangles (NFTs). Aggregates are composed of hyperphosphorylated tau protein that is more prone to aggregation. The pathology of AD is also linked to disturbed copper homeostasis, which promotes oxidative stress (OS). Copper imbalance is widely observed in AD patients. Deregulated copper ions may initiate and exacerbate tau hyperphosphorylation and formation of β-sheet-rich tau fibrils that ultimately contribute to synaptic failure, neuronal death and cognitive decline observed in AD patients. The present review summarizes factors affecting the process of tau aggregation, conformational changes of small peptide sequences in the microtubule-binding domain required for these motifs to act as seeding sites in aggregation, and the role of copper in OS induction, tau hyperphosphorylation and tau assembly. Better understanding of the various factors that affect tau aggregation under OS conditions may reveal new targets and novel pharmacological approaches for the therapy of AD.